EXPERIENCE QUALITY, SATISFACTION, AND LOYALTY FOR HAIR AND BEAUTY SALON - Dina Kamila (Politeknik Negeri Bandung, 2018)
This study focused on hair and beauty salon consumption and aimed to investigate the relationship between experience quality, satisfaction, and customer loyalty. The research model investigates the relevant relationship among the construct by using Partial Least Square (PLS) method by computational assistance program WarpPLS. The findings of this study are based on the views of 406 respondent completed a survey conducted at various hair and beauty salon in Indonesia including Anata Hair and Beauty salon, Rudi Hadisuwarno, Johny Andrean, Martha Tilaar and other. The result will assist hair and beauty salon managers in developing and implementing a competitive customer experience strategy that can enhance customer satisfaction, customer loyalty, growth, and sustainability.